Computer-Supported Collaborative Decision-Making - Filip, Florin Gheorghe; Zamfirescu, Constantin-Bălă.; Ciurea, Cristian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This is a book about how management and control decisions are made by persons who collaborate and possibly use the support of an information system. The decision is the result of human conscious activities aiming at choosing a course of action for attaining a certain objective (or a set of objectives). The act of collaboration implies that several entities who work together and share responsibilities to jointly plan, implement and evaluate a program of activities to achieve the common goals. The book is intended to present a balanced view of the domain to include both well-established concepts and a selection of new results in the domains of methods and key technologies. It is meant to answer several questions, such as: a) "How are evolving the business models towards the ever more collaborative schemes?"; b) "What is the role of the decision-maker in the new context?" c) "What are the basic attributes and trends in the domain of decision-supporting information systems?"; d) "Which are the basic methods to aggregate the individual preferences?" e)"What is the impact of modern information and communication technologies on the design and usage of decision support systems for groups of people?". .
Collaboration and Decision-making in Context -- Decision Support Systems -- Collaborative Activities and Methods -- Essential Enabling Technologies -- Applications.
Keywords: Control engineering; Robotics; Automation; Computational intelligence; Operations research; Control, Robotics, Automation; Computational Intelligence; Operations Research and Decision Theory